A New Method for Covering Defects over Forearm with Extern Al Fixator Apparatus in Position - Pathil, D. L.; Kumta, S. M.; Thatte, R. L. (Indian Journal of Plastic Surgery, 1987)
A case of a mutilating injury of the forearm treated with a multiple entry A. O. external fixator was provided with a flap cover from the abdomen. The manoeuvre used to achieve the flap cover, along with a brief discussion is being presented.